New insights into the Mesolithic and Neolithic layers of the Darkveti rock shelter in the Imereti Region, Western Georgia - Guram Chkhatarashvili; Nikoloz Tskvitinidze; Nikoloz Tsikaridze; James A. Davenport; Michael D. Glascock (Documenta Praehistorica)
The Darkveti multi-layered site in the Imereti region of Georgia offers valuable insights into prehistoric human activity. Despite extensive research conducted in the 1960s and 1970s by Lamara Nebieridze, certain aspects of the site's chronology and inhabitants' mobility remained unclear. This study aims to address these gaps through collaborative, interdisciplinary research involving Georgian and foreign scientists. The primary objective is to precisely date the cultural layers belonging to the Mesolithic and Neolithic epochs using absolute dating methods. By combining archaeological evidence with palaeontological, geoarchaeological, and palaeobotanical data, this study aims to reconstruct the palaeoenvironment and subsistence strategies of the Darkveti inhabitants. Additionally, the analysis of stone tools and lithic raw materials will shed light on technological developments and possible connections with neighbouring regions. The findings will contribute to a better understanding of the cultural dynamics, mobility patterns, and adaptations of prehistoric communities in the Imereti region and the wider Caucasus.